Pertanggung Jawaban Pidana dan Kaitannya dengan Pertanggungjawaban Perdata Pelaku Penelantaran Rumah Tangga - Maryati Maryati; Usman Usman (Wajah Hukum, 2020)
The neglect of the household in its realm belongs to the realm of civil liability, but can have implications for criminal liability. This article aims to explain the relationship between civil and criminal liability for the neglect of the household. Civil liability of perpetrators of household neglect is based on losses due to neglect of the household, so the perpetrators are required to compensate. Peberian compensation based on the principle of law that the obligations of the husband in accordance with their abilities. Criminal liability is based on the fulfillment of the actus reus element in Article 9 of the Domestic Violence Act, and the mens rea element is intentional or negligent of the perpetrator. Fulfillment of civil liability perpetrators of neglect of the house in khakhatnya eliminate the offensive nature of the perpetrator, so that it should be the basis for stopping the criminal justice process, but there is no legal mechanism that regulates. That is possible through probationary criminal institutions (Article 14a KUHP). For this reason, it is necessary to have rules related to restorative justice and the application of the principle of ultimum remedium in the rules on domestic protection that prioritize civil accountability.